Windrowing and prismatic baling of sugar cane vegetal residues: Some operational parameters and energetic efficiency - Ripoli, M. L C [UNESP]; Torrezan, H. F.; Ripoli, T. C.; Gamero, Carlos Antonio [UNESP] (My University, 2004)
It was evaluated the energetic efficiency and operational parameters of a windrowing and prismatic baling, both from CASE NEW HOLLAND® operations in sugarcane vegetal residues (green leaves, dry leaves and tops) picked mechanically in green cane. The area belongs to COSTA PINTO MILL (COSAN® Group) which was harvested mechanically by combines in the State of Sao Paulo, Brazil. The geographic location of the area is: Latitude 22°40'30S, Longitude 47°36'38W and Altitude of 605m. The variety was RB 82-5336, planted in 1.40m row spacing, with 78t.ha-1 yield. The vegetal residues analysis obtained 69.93% of leaves, 21.44% of stalks fractions, 2.27% of tops and 6.36% of total strange matter. The vegetal residues values were: gross heat of 18.43MJ.kg-1, low heat of 17.00MJ.kg'1 and useful heat of 12.94MJ.kg-1. The vegetal residues average energetic potential was 342.48GJ.ha-1. The treatments were simple, double and triple windrowing. The use of the rake and prismatic baler to pick up the residues was viable. The simple windrowing treatment presented the best results: effective capacity of 83.06t.ha-1, fuel consumption of 0.18L.t -1 and 99.95% of positive energetic efficiency. The bales obtained in the treatment of triple windrowing presented the largest specific mass average of 221.11kg.m-3. The soil amount in the bales increased with successive windrowing. The baling operation in the triple windrowing treatment obtained better results, presenting the effective capacities of 20.29t.h -1 and 1.45ha.h-1 and fuel consumption of for baled in 1.37L.t-1. The high total energetic efficiency of 99.53% indicates that is technically viable the withdrawal of the vegetal residues.
Keywords: Baling; Energy efficiency; Evaluation; Sugar cane; Trash; Windrowing; Fuel consumption; Harvesting; Plants (botany); Soils; Prismatic baling; Vegetal residues; Fuels; Leaves; Soil; Sugar Cane